Functional Freeze in Urban India: An Integrative Literature Review of Stress, Environment and Workplace Experience - Srinivas, Duhitha; Ghosh, Sanjukta (International Journal of Engineering and Management Research, 2025)
Stress is a physiological and psychological response to perceived threats in the environment, through which the body and mind attempt to protect themselves. Among the recognised stress responses: fight, flight, fawn, and freeze, this study focuses on freeze, specifically its contemporary subtype, functional freeze, within the Indian urban context. Freeze has been understood as an acute response to life-threatening situations; emerging research in clinical psychology suggests that persistent, non-life-threatening stressors can evoke a state of functional freeze. In this state, individuals meet everyday demands outwardly while experiencing internal disengagement, emotional flattening, and a reduced capacity to process stress. In urban India, sensory overload, crowding, limited access to restorative natural spaces, fast-paced routines, and increasing dependence on digital devices for work and education can disrupt normal stress-recovery cycles. These conditions create a context in which functional freeze may emerge and persist. This study synthesises perspectives from behavioural neuroscience, urban environmental research, and self-regulation to develop a systemic understanding of functional freeze. The review extends into organisational settings, examining how functional freeze may manifest in workplaces through patterns such as presenteeism, decision inertia, and mental withdrawal, despite apparent productivity. From the standpoints of human resource management, organisational behaviour and transformation, functional freeze recognition has propositions for employee wellbeing, sustainable performance, and workplace culture.